Productivity of sugar cane genotypes in response to the limestone application in microclimate of the brazilian semiarid (Research, Society and Development, 2021)
For the sugarcane field to produce satisfactorily, it is necessary to cultivate sugarcane genotypes that are adapted to the edaphoclimatic conditions of the region, in addition, it is also necessary to correct the soil so that the plant can extract from the soil all the nutrients necessary for its development. The objective of this work was to evaluate the productivity of sugarcane genotypes cultivated with and without liming during the cane-plant and ratoon cane cycles. The experimental design used was in DBC, with 4 replications, in a 10 x 2 factorial scheme, with 10 sugarcane genotypes and two lime managements (with and without application). The amount of lime applied was calculated based on the base saturation elevation formula with the result of the soil analysis, using 4.5 t ha-1 of lime incorporated into the soil in the sugarcane plant and 2.8 t ha- 1 on the surface of the cane. Plant height, average stem diameter, number of stems per meter, number of internodes, ºBrix, productivity were evaluated. The data were subjected to analysis of variance and the means compared to each other by the Scott-Knott test. The results show that in the cane plant, limestone promoted an increase in plant height, stem diameter, stems per meter, and productivity. In soca cane, limestone positively influenced the number of stems per meter, and productivity, with ° Brix the only variable negatively affected. The genotypes that responded best to liming were RB93509, RB002754, RB962962, RB992506 and SP79-1011.